PERAN KEPALA SEKOLAH DALAM MENGEMBANGKAN KEPRIBADIAN PESERTA DIDIK MELALUI KEGIATAN KEAGAMAAN DI MADRASAH IBTIDAIYAH NURUL HUDA MULYOREJO KOTA MALANG - Siti Zulaikha; Muhammad Hanief; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Schools as formal institutions in providing Islamic religious learning must have a learning curriculum development that considers everything related to student competencies. This study discusses the role of the principal in developing student personality through religious activities in the Madrasah Ibtidaiyah Nurul Huda Mulyorejo, Malang. The method in this study uses qualitative methods, the type of case study. The subjects of this study are the principal, the teacher. From the findings obtained from religious activities through correct habituation that is when meeting with the teacher, students give a smile while kissing their hands. Both the habituation of Dhuha prayer and Dhuhr prayer in congregation ie students have a sense of responsibility and discipline in carrying out worship. And third is reading using the ummi method, that is, students are more active and read according to the tawjid in the parents' monitoring and monitoring book. The role of the principal in developing student personality through religious activities is to set an example, provide motivation, provide facilities, give gifts and conduct supervision. The things that need to be considered are about the habit of religious activities being carried out well, but the school can improve again through inculcation of other Islamic values.